4x-3(2x-3)=11

Simple and best practice solution for 4x-3(2x-3)=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-3(2x-3)=11 equation:


Simplifying
4x + -3(2x + -3) = 11

Reorder the terms:
4x + -3(-3 + 2x) = 11
4x + (-3 * -3 + 2x * -3) = 11
4x + (9 + -6x) = 11

Reorder the terms:
9 + 4x + -6x = 11

Combine like terms: 4x + -6x = -2x
9 + -2x = 11

Solving
9 + -2x = 11

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + -2x = 11 + -9

Combine like terms: 9 + -9 = 0
0 + -2x = 11 + -9
-2x = 11 + -9

Combine like terms: 11 + -9 = 2
-2x = 2

Divide each side by '-2'.
x = -1

Simplifying
x = -1

See similar equations:

| 0.7(3x-5)+3.9=14.5 | | -9=3+6k | | 3b-2(b+4)=8(b-1) | | x-4+6x-8x=3 | | 3(4X-3)=-81 | | 8(2x+3)-5=16x+19 | | -7(3v+6)=-7v+32 | | 3(x-7)=23-(3x+2) | | 6(4X+4)=24 | | -63+105= | | 18-m=9+3 | | -37=3w+11-7w | | -9*7= | | 4(5-n)=-16 | | 7y-12=4y+6 | | y=100+.80y+100 | | 3-(x+7)=23-(3x+2) | | 7(x+3)=4x | | -2.3x=34.04 | | 7(x+3)=4c | | 3(x+4)=35 | | -8x+4x+19-12x= | | 7(x+3)=4b | | 0+41=51 | | 3n-9=-9 | | .8x+9=.6x-6 | | 7x-10=-21x-4 | | (N-13)+4=5 | | 30n-40=29 | | 9-2u=15-4u | | 14n=29 | | 7h-5=4h+22 |

Equations solver categories